Study of Existing Pedagogical Practices, Issues and Challenges of Inclusive Education in Chandigarh - Kaur, Harpreet; Bansal, Sneh (INDIAN EDUCATIONAL REVIEW, 2019)
‘Inclusive education’ or ‘Education for All’ has taken centre stage within the human rights framework. In inclusive education, children with disabilities are taught in regular schools with their age and grade peers with the support services provided within the school system. Inclusion involves valuing diversity in teaching groups and the adaptation of teaching approaches to support them. Inclusion cannot go very far without developing the capacity of schools to respond to diversity among children.